Epidemics, inequality and poverty in preindustrial and early industrial times - Guido Alfani (European Historical Economics Society (EHES), 2020)
Recent research has explored the distributive consequences of major historical epidemics, and the current crisis triggered by Covid-19 induces to look at the past for insights about how pandemics can affect inequalities in income, wealth, and health. The fourteenth-century Black Death, which is usually credited to have led to a significant reduction in economic inequality, has attracted the greatest attention. However, the picture becomes much more complex if other epidemics are considered. This article covers the worst epidemics of preindustrial times, from Justinian's Plague of 540-41 to the last great European plagues of the seventeenth century, as well as the cholera waves of the nineteenth. It shows how the distributive outcomes of lethal epidemics do not only depend upon mortality rates, but are mediated by a range of factors, chief among them the institutional framework in place at the onset of each crisis. It then explores how past epidemics affected poverty, arguing that highly lethal epidemics could reduce its prevalence through two deeply different mechanisms: redistribution towards the poor, or extermination of the poor. It concludes by recalling the historical connection between the progressive weakening and spacing in time of lethal epidemics and improvements in life expectancy, and by discussing how epidemics affected inequality in health and living standards.
Keywords: D31; D63; I14; I30; J11; N30; N33; 330; epidemic; pandemics; inequality; poverty; plague; Black Death; cholera; preindustrial times; wealth concentration; middle ages; early modern period